The Impact of the Command and Self-Check Teaching Styles in Goal Orientations, Perceived Motivational Climate and Perceived Athletic Ability in the Elementary - Patmanoglou, Στυλιανός; Digelidis, Νικόλαος; Mantis, Κωνσταντίνος; Papapetrou, Λαμπρινή; Mavidis, Αλέξανδρος (Inquiries in Physical Education and Sport, 2007)
The aim of the present study was to evaluate two teaching styles for the more effective teaching of tennis at the elementary level. 307 students participated in this study (5th and 6th graders, 160 boys, 147 girls) from 7 elementary schools of Northern Greece, with age ranging from 11-12 years old (Μ=11±6). The pupils were divided into three groups: a) the first experimental group attended 10 tennis lessons (once a week) based on the command teaching style, b) the second experimental group attended 10 tennis lessons based on the selfcheck teaching style and c) the control group followed the typical PE curriculum. There were two times of measurement before and after the completion of the intervention. The internal consistency of subscales was at an acceptable level (α>.60). The results deriving from the analysis of repeated measurements showed that there were statistically significant differences between the two genders with regard to a) ego orientation and b) perceived athletic ability. Also, differences were found between the initial and final measurement with reference to the attitudes towards tennis lessons.